Edukacja w kryzysie. Próba wstępnej charakterystyki i oceny - Szmyd, Jan (Rocznik Pedagogiczny, 2020)
The contemporary education faces the worsening structural crisis. It is the real e d u c a t i o n a l c r i s i s – it’s being exposed at a scale not experienced before. This crisis is determined with the civilization and economy. It’s being invoked with expanded scientific-technology and information civilization and co-related new neoliberal socio-economic system. Thus, the educational crisis is global, as it’s determinants are. The article focus on the main manifestations of the educational crisis: 1) the excessive orientation of higher education programmes on the utilitarian (professional, vocational) knowledge at the expense of the general (cultural and humanistic) knowledge, which is driven by the economic growth; 2) the collapse of the great pedagogical narratives and ideas; 3) the regress of academic identity of the most of universities; 4) the increasing dysfunction of the classical models of school, teacher and upbring- ing; 5) the permanent decrease of the quality of the general education and upbringing. The contemporary educational crisis is the major threat to the comprehensive and harmonious hu- man development, in a sense it’s the crisis of the man himself.